Sociolinguistic studies of Slovene emigration issues - Šabec, Nada (Dve domovini, 1993)
The author presents the achievements of research into Slovene emigration in the field of sociolinguistics and points to the directions of future development. The point of contact between sociolinguistics and emigration is the study of bi- and multi- lingualism, in this case the linguistic tie between Slovene and the dominant language of the country of immigration. In adition to a critical evaluation of research to date (e.g. R.L. Lenček, F.J. Kess, J. Paternost and others) the author also speaks of her own work in some detail.
Keywords: angleščina; bilingualism; dvojezičnost; English; jezikovni preklop; Slovene; slovenski izseljenci; slovenščina; sociolinguistics; sociolingvistika; United States of America; ZDA